Mino-Mnaamodzawin: Achieving Indigenous Environmental Justice in Canada - McGregor, Deborah (Osgoode Digital Commons, 2018)
This article explores the potential for advancing environmental justice (EJ) theory and practice through engaging with Indigenous intellectual traditions. When EJ is grounded in Indigenous epistemological and ontological foundations, a distinct EJ framework emerges, leading to a deeper understanding of Indigenous EJ and to a renewed vision for achieving it. I highlight the emergence of the Anishinaabe philosophy referred to as mino-mnaamodzawin (“living well” or “the good life”), common to several Indigenous epistemologies, that considers the critical importance of mutually respectful and beneficial relationships among not only peoples but all our relations (including all living things and many entities not considered by Western society as living, such as water and Earth itself). Mino-mnaamodzawin is suggested as a foundational contributor to a new ethical standard of conduct that will be required if society is to begin engaging in appropriate relationships with all of Creation, thereby establishing a sustainable and just world.